Impact of implementing an EMR on physical exam documentation by ambulance personnel - Katzer, R.; Barton, D.J.; Adelman, S.; Clark, S.; Seaman, E.L.; Hudson, K.B. (Applied Clinical Informatics, 2012)
Objective: Georgetown University has a student run Emergency Medical Services (EMS) organization with over 100 emergency medical technicians (EMTs). We set out to determine whether implementing an electronic patient care report (ePCR) system was associated with improved physical exam documentation.Methods: This study evaluated documentation of the physical exam on prehospital patient care reports (PCRs). An ePCR system was implemented. ePCR documentation was compared to that of the previously used paper PCRs. This study looked retrospectively at 154 PCRs. 77 were hand written PCRs from before the electronic system. The PCRs involved chief complaints that were primarily respiratory, neurologic, or both. 77 ePCRs of matching chief complaint categories were used for comparison. Each chart was reviewed for completion of certain physical exam findings. The mean percentage of documented components from the ePCRs was compared to that of the hand written PCRs. The null hypothesis was that the absolute increase in the mean was not more than 20 percent. The two exclusion criteria were PCRs completed by study investigators after the design of the project and partially or completely missing PCRs.Results: The absolute increase in mean physical exam component documentation was 36% (95% CI = 29–43%). A weighted kappa of 0.894 showed very good agreement between chart reviewers.Conclusions: This study rejected the null hypothesis that the ePCR system was associated with a mean increase of no more than 20%. It observed increase in physical exam documentation. Limitations of this study included the inability to determine whether documentation of physical exam findings reflected performance of the physical exam, and what components of the ePCR system bundle were responsible for the increase in physical exam component documentation.
Keywords: Documentation; quality improvement; emergency medical technicians; universities; emergency medical services; electronic health records